2002
DOI: 10.1034/j.1600-0722.2002.21247.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal pathways involved in the production of MMP‐1 and MMP‐3 in human gingival fibroblasts

Abstract: Periodontitis is associated with enhanced production of cytokines, prostaglandins and matrix metalloproteinases (MMPs). The aim of this study was to investigate the production and regulation of MMP-1 and MMP-3 in human gingival fibroblasts challenged with the cytokines interleukin-lbeta (IL-1beta), tumor necrosis factor alpha (TNFalpha) or epidermal growth factor (EGF). The results showed that gingival fibroblasts constitutively produce MMP-1 and MMP-3, and that the cytokines IL-1beta, TNFalpha and EGF increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 35 publications
8
95
1
7
Order By: Relevance
“…Our results are consistent with the previous observation that exogenous PGE 2 up-regulates MMPs in gingival fibroblasts (Sakaki et al, 2004). Other studies have reported that PGE 2 mediates IL-1β-induced MMP-1 up-regulation in tendon and gingival fibroblasts (Domeij et al, 2002;Tsuzaki et al, 2003). It is noted that tendon consists predominantly of collagen type I with a triple helical structure that resists general proteolytic degradation but is susceptible to MMPs.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the previous observation that exogenous PGE 2 up-regulates MMPs in gingival fibroblasts (Sakaki et al, 2004). Other studies have reported that PGE 2 mediates IL-1β-induced MMP-1 up-regulation in tendon and gingival fibroblasts (Domeij et al, 2002;Tsuzaki et al, 2003). It is noted that tendon consists predominantly of collagen type I with a triple helical structure that resists general proteolytic degradation but is susceptible to MMPs.…”
Section: Discussionsupporting
confidence: 93%
“…However, the induction of MMP1 by IL-1b was less powerful in comparison with the MC medium, suggesting the involvement of other factors derived from macrophages. The stimulatory effects of IL-1b on MMP1 and MMP3 release have been described in other cell types such as chondrocytes (Liacini et al, 2005) and gingival fibroblasts (Domeij et al, 2002). In the present study, TNFa alone also induced a small increase in protein release of both MMPs but the induction was much less potent than the MC medium, and this observation suggests that other macrophagederived factors, such as IL-1b, could be the key mediators.…”
Section: Discussionmentioning
confidence: 64%
“…MMP-1 is an inducible enzyme, and its gene transcription is modulated by several cytokines that play a central role in inflammation (Domeij et al 2002). MMP-1 mRNA levels have been shown to be significantly increased during the course of gingivitis or periodontitis in human gingival tissue (Aiba et al 1996;Ejeil et al 2003).…”
Section: Effects Of Go On Mmp-1mentioning
confidence: 99%